Feasibility of Potato Farming in Pakis Sub-District, Magelang District - Rahmawati Nur; Thalita Kanaya Salsabila (E3S Web of Conferences)
Potato crops play an important role in providing food and can generate income, employment opportunities, and livelihoods through potato farming. This study aims to determine the costs, profit receipts and feasibility of potato farming in Pakis District, Magelang Regency. The research location in Pakis sub-district was chosen because it has the largest land area but low production in Magelang district. The number of respondents was 50 farmers who were taken randomly from 113 potato farmers in Pakis sub-district. The analysis technique used descriptive analysis of cost, revenue and profit analysis as well as R/C analysis, capital productivity, labour productivity and land productivity. The results showed that on a land area of 1,830 m2 potato farming requires a total cost of 16,760,225. The revenue obtained was IDR 30,475,380 and the profit was IDR 13,902,877. Based on the results of the R/C value of 1.84, capital productivity of 84%, labour productivity of IDR 261,578/workday, and land productivity of IDR 7,597/m2, potato farming in Pakis District is feasible. Therefore, it is expected that potato farmers can improve and develop potato cultivation in order to generate greater profits.